MiR-210 and miR-155 as potential diagnostic markers for pre-eclampsia pregnancies. Issue 28 (July 2017) - Gan, Lu; Liu, Zheng; Wei, Ming; Chen, Yulong; Yang, Xiaomei; Chen, Lihong; Xiao, Xiaomin
Abstract : Abstract: Pre-eclampsia (PE) is one of the leading causes of maternal and neonatal morbidity and mortality. In recent years, many studies have shown that microRNAs (miRNA) play important roles in the development of PE. However, the molecular pathogenesis of PE remains unknown. In the present study, we performed a case–control study to verify the differential expression of 4 candidate miRNAs (miR-210, miR-155, miR-125b-5p, and miR-125a-5p) in 20 PE pregnancies and 20 healthy pregnancies. The real-time quantitative reverse transcriptase-polymerase chain reaction has been utilized to estimate the C t values in both groups. Our results have shown that miR-210 and miR-155 were upregulated in serum of PE pregnancies, which suggest a potential association between these 2 miRNAs and the pathogenesis of PE. Further studies showed that the area under the receiver operating characteristic curve (AUC) of miR-210 and miR-155 were 0.750 and 0.703, respectively. The AUC of the expression ratio of miR-210 (serum/urine) and miR-155 (serum/urine) were 0.761 and 0.718, respectively. Moreover, 24-hour urine proteins have positive correlation with urine miR-210 and miR-155. Our findings indicated that serum miR-210 and miR-155 could be 2 sensitivity and specificity biomarkers for the diagnosis of PE while urine miR-210 and miR-155 both could be used to evaluate the severity of kidney injury. Using these miRNAs may provide a novel diagnosis method for identifying pregnant women who are at risk for developing PE.